School engagement and implications for future opportunities: Roma students’ trajectories - Moreira, Tânia; Rosário, Pedro; Ferreira, Márcia; Pereira, Armanda; Fuentes, Sonia (Frontiers in Psychology, 2025)
IntroductionRoma students often face challenges such as discrimination and social exclusion that hinder their school engagement. However, little is known about how their engagement changes over time and how this affects future life opportunities.MethodsThis qualitative, longitudinal study followed 13 Roma students (ages 10–14) during a critical school transition (5th to 6th grade). Semi-structured interviews were conducted at the beginning and end of the school year and analyzed thematically.ResultsFindings revealed that students maintained strong connections with peers and the school environment but showed weaker engagement in classroom learning. Over time, declining teacher relationships, reduced attendance, and limited academic support at home further diminished engagement. These patterns were linked to a low perceived value of formal education and restricted aspirations shaped by cultural norms.DiscussionThe study highlights how social, familial, and cultural factors intersect to influence Roma students’ engagement trajectories. Interventions are needed that both build on cultural strengths and address motivational beliefs and structural barriers to enhance long-term educational opportunities.